An Efficient Selectfluor-Mediated Oxidative Thio- and Selenocyanation of Diversely Substituted Indoles and Carbazoles. (2nd January 2019) - Abonia, Rodrigo; Gutierrez, Luisa F.; Zwarycz, Angela T.; Correa Smits, Sebastián; Laali, Kenneth K.
Abstract : A facile Selectfluor-mediated oxidative method for direct introduction of SCN and SeCN groups into diversely substituted indoles and carbazoles is described, by employing readily available thiocyanate and selenocyanate salts, and the scope of the method is underscored by providing 24 examples. The feasibility to sequentially introduce SCN followed by SeCN on a carbazole framework and to synthesize the corresponding S-tetrazole and Se-tetrazole derivatives is also demonstrated.